2008
DOI: 10.1088/1126-6708/2008/06/101
|View full text |Cite
|
Sign up to set email alerts
|

Exact multi-restricted Schur polynomial correlators

Abstract: We derive a product rule satisfied by restricted Schur polynomials. We focus mostly on the case that the restricted Schur polynomial is built using two matrices, although our analysis easily extends to more than two matrices. This product rule allows us to compute exact multi-point correlation functions of restricted Schur polynomials, in the free field theory limit. As an example of the use of our formulas, we compute two point functions of certain single trace operators built using two matrices and three poi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
133
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(136 citation statements)
references
References 53 publications
1
133
0
Order By: Relevance
“…Inspired by the Gauss Law which will arise in the world volume description of the giant graviton branes, the authors of [23] suggested operators in the gauge theory that are dual to excited giant graviton brane states. This inspired idea was pursued both in the case that the open strings are described by an open string word [24][25][26] and in the case of minimal open strings, with each open string represented by a single magnon [27,28]. The operators introduced in [24,27] are the restricted Schur polynomials.…”
Section: Jhep03(2016)156mentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the Gauss Law which will arise in the world volume description of the giant graviton branes, the authors of [23] suggested operators in the gauge theory that are dual to excited giant graviton brane states. This inspired idea was pursued both in the case that the open strings are described by an open string word [24][25][26] and in the case of minimal open strings, with each open string represented by a single magnon [27,28]. The operators introduced in [24,27] are the restricted Schur polynomials.…”
Section: Jhep03(2016)156mentioning
confidence: 99%
“…each open string is a single magnon. In this case one must use the correlators computed in [27,28] as opposed to the correlators computed in [24]. The case with distinguishable open strings is much simpler since when the correlators are computed, only contractions between corresponding open strings contribute; when the open strings are identical, it is possible to contract any two of them.…”
Section: Jhep03(2016)156 8 Links To the Double Coset Ansatz And Open mentioning
confidence: 99%
“…For a nice recent review see Ramgoolam [24]. Finally a product rule for restricted Schur polynomials has been obtained in [25]. Together with the two-point function derived in [4] this allows us to derive higher point functions.…”
Section: Introductionmentioning
confidence: 99%
“…New bases of gauge-invariant operators have been discovered, which diagonalize the tree-level two-point functions at finite N c [5][6][7][8]; see [9] for a review.…”
Section: Jhep06(2017)055mentioning
confidence: 99%
“…The convention of [24] is used here for efficient evaluation. 7 This formula is elaborated further as the highest weight generating function [25].…”
Section: Jhep06(2017)055mentioning
confidence: 99%